Peran Pengelolaan Likuiditas dan Efisiensi Aktivitas Usaha terhadap Kinerja Keuangan UMKM Fashion: Studi Kasus di Ambarawa, Kabupaten Semarang - Reliani Zai; Syamsul Hadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze the role of liquidity management and business activity efficiency in improving the financial performance of fashion-sector micro, small, and medium enterprises (MSMEs) in Ambarawa, Semarang Regency. This study employs a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, direct observation, and documentation from purposively selected fashion MSME actors and were analyzed using thematic analysis. The findings indicate that liquidity management plays a crucial role in maintaining operational continuity and financial stability, although its implementation remains relatively simple and reactive to fluctuations in market demand. Business activity efficiency is achieved through order-based production, raw material cost control, and flexible labor utilization, which effectively help reduce costs and mitigate financial risks. Theoretically, this study contributes to the MSME financial management literature by emphasizing context-based processes and practical financial management practices. Practically, the findings provide implications for MSME actors and stakeholders in designing sustainable liquidity management and business efficiency strategies to enhance the financial performance of fashion MSMEs.